2015
DOI: 10.1007/s11999-014-4112-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Previous Pelvic Osteotomy Compromise the Results of Periacetabular Osteotomy Surgery?

Abstract: Background As the Bernese periacetabular osteotomy (PAO) has grown in popularity, specific indications and the results in patients treated for those indications need to be evaluated. Currently, although many patients undergo PAO after having had prior pelvic osteotomy, there is limited information regarding the efficacy of the PAO in these patients.Questions/purposes The purpose of this study was to compare the (1) early pain, function, activity, and quality of life outcomes; (2) radiographic correction; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…14 Other studies examining the outcomes of PAO in the revision setting have focused on patients who had undergone previous pelvic osteotomy. 2,26,33 In a multicenter study, Stambough et al 33 found that patients who had undergone prior pelvic osteotomy did reach a threshold for clinical improvements; however, the overall magnitude of improvements in the pain and functional domains was smaller at a mean 2.5 years of follow-up relative to a group of patients without prior surgery. Polkowski et al 26 also found improvements after PAO in patients who had undergone prior pelvic osteotomy; however, the mean mHHS improved only 11 points from preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…14 Other studies examining the outcomes of PAO in the revision setting have focused on patients who had undergone previous pelvic osteotomy. 2,26,33 In a multicenter study, Stambough et al 33 found that patients who had undergone prior pelvic osteotomy did reach a threshold for clinical improvements; however, the overall magnitude of improvements in the pain and functional domains was smaller at a mean 2.5 years of follow-up relative to a group of patients without prior surgery. Polkowski et al 26 also found improvements after PAO in patients who had undergone prior pelvic osteotomy; however, the mean mHHS improved only 11 points from preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who failed to improve by MIC at final follow-up fell into 3 primary groups: patients undergoing revision hip preservation surgery at the time of PAO; patients with a postoperative complication; or patients with a more complex deformity or collagen disease in addition to their acetabular dysplasia. PAO in the setting of prior hip preservation attempts may have inferior outcomes to the nonrevision setting (38, 39). The effect of prior hip arthroscopy on outcomes after PAO remain unclear, however, Kain et al (40) did not find a prior hip arthroscopy compromises functional outcomes of PAO.…”
Section: Discussionmentioning
confidence: 99%
“…15,57 Our study had some limitations in determining dysplasia measurements through radiographs, which have been highlighted in previous studies. 44,49 Although we assessed actabular dysplasia in 3 dimensions using Hip2Norm software based on AP pelvis radiographs, 56 3-dimensional computed tomography reconstruction, which was not available for all our patients, would provide more detailed analyses. In addition, because of the influence of pelvic incidence on acetabular orientation, the degree of overlap between what might be considered an essentially normal acetabular orientation versus dysplastic orientation can still vary from patient to patient, further emphasizing the importance of physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is that our results are still short term; hence, longer term longitudinal studies will be needed to further validate our findings in regard to joint survivorship. 30,44 Additionally, despite the HOOS being validated for use across multiple hip abnormalities, because our patients were commonly young and healthy with active lifestyles, we must consider the possible presence of floor or ceiling effects in our interpretation of PROM scores. 30 What represents a ''healthy/sustainable'' relationship between the femoral head and acetabulum is complex, as there are a near infinite number of bony morphological and dynamic/functional configurations that can exist along a spectrum of stability.…”
Section: Discussionmentioning
confidence: 99%